Особливості імунних реакцій дітей, яких вигодовують матері-курці - Боярська, Людмила Миколаївна; Герасімчук, Тетяна Сергіївна; Котлова, Юлія Валентинівна; Boyarskaya, L. N.; Herasimchuk, T. S.; Kotlova, Yu. V.; Боярская, Л. Н.; Герасимчук, Т. С.; Котлова, Ю. В. (Вищий державний навчальний заклад України «Українська медична стоматологічна академія», 2015)
Залишається відкритим питання про раціональність годування грудним молоком жінками, які курять. Ìета роботи – вивчення імунологічних змін у дітей матерів-курців при природному і штучному вигодовуванні на підставі аналізу імунологічних досліджень у 47 немовлят і визначенні ролі прозапального IL-1-α в молоці 120 матерів при палінні. Встановили імунний дисбаланс із збільшенням показників вродженої і специфічної імунної відповіді, які були більш значними у дітей-пасивних курців при штучному вигодовуванні. Незважаючи на прозапальних ефект IL-1-α материнського молока у матерів-курців, воно має протективну дію на імунну відповідь малюків і дозволяє зменшити у них напругу гіперреактивності імунної відповіді в умовах пасивного куріння. Breastfeeding of babies with mothers-smokers leaves many controversial questions. Macrophages of human milk produce whole range of interleukins (IL) which has a high potential impact on the immune system. IL-1-α has a distinct immunostimulatory effect, that causes the immune defense system with a level of inflammation. Under physiological conditions, IL-1-α is able to detect hyperreactivity immune response. The increasing proinflammatory cytokine IL-1-α in serum of adult smokers. There is no clear answer to the content in colostrum and milk of women smokers cytokine IL-1-α and its impact on infant immune smoking mothers. The aim – to study the immunological changes in children of mothers-smokers. Object and methods. Tested the hypothesis of a possible increased «stimulate» the immune response with proinflammatory IL-1-α, which is contained in human milk of mothers nursing-smokers. ompared concentrations of IL-1-α in the milk of 120 lactating women: the first group comprised women smokers and women – passive smokers (n = 46), the second group included women who do not smoke themselves and the families that do not smoke (n = 74). Mathers- smokers considered smokers more than 5 cigarettes daily for at least 5 years. Milk was collected in the morning 1 hour after smoking cigarettes. IL-1-α were determined by ELISA analysis using polyclonal antibodies to IL-1-α ELISA set Cat. Number VMS243 / 2 HumanIL-1 alpha Platinum ELISA Bender Med System. The next phase of the study was analyzing the immune responses of passive smokers who saved breastfeeding in the early period of convalescence after acute respiratory illness. We studied the immunological 1-st level 47 children aged 8 to 12 months babies whose mothers were smoked. Children experimental group (group № 1) receiving mother’s milk (n = 24), children of the comparison group (group № 2) were bottle-fed (n = 23). The criterion of exclusion from the study – the availability of primary immunodeficiencies. For statistical treatment used the program «Statistica – 2006» (StatSoftInc., № AXXR712D833214FAN5). Evaluation of conducted descriptive method (median (Me), limits quaterly segments | 25 % -75 % |); comparing two independent groups was performed using U-criterion Mann-Whitney, reliability considered available at p < 0.05. Designated statistically significant (p < 0.05) higher levels of proinflammatory IL-1-α in the milk of mothers smokers – 0,31 | 0,21-0,49 | (pg / ml). Installed increased proinflammatory potential of immune reactivity (by increasing the level of white blood cells, NBT-test, immunoregulatory index, T lymphocytes: CD8 +, CD19 +, CD25 +, serum IgG) (p < 0.05) during early convalescence under conditions of passive smoking children were bottle-fed compared with children passive smokers that vyhodovuvalys naturally. Breastfeeding, despite elevated levels of proinflammatory IL-1-α in the milk of mothers smokers can reduce stress hyperreactive immune response from children that are living in conditions of passive smoking.
Особенности иммунных реакций детей, которые вскармливаются курящими матерями
Immunoreaction Features of Children, Feeded by Mothers smokers
Keywords: діти; імунітет; пасивне куріння; природнє вигодовування; children; immunity; passive smoking; дети; иммунитет; breast-feeding; пассивное курение; естественное вскармливание